Life-time experience of violence among women and girls living with disability in Nepal - Padam Simkhada; Sapana Basnet; Shaurabh Sharma; Edwin van Teijlingen; Sharada Prasad Wasti; Tikadevi Dahal; Joshua Okyere; Ram Chandra Silwal; Manita Pyakurel (PLoS ONE, 2025)
Background Violence against women and girls with disabilities remains a serious, yet underexplored, global concern. This paper aims to investigate the prevalence and factors associated with life-time experience of violence within this vulnerable population in Nepal. Methods This cross-sectional study was conducted in 28 municipalities representing all seven provinces as well as all three ecological regions of Nepal. A total of 1,294 women and girls with disability aged 15–59 years participated in this study. Data were collected in the period August to October 2021. This was done by trained enumerators using the KoBo application on smartphones or tablets. Both written and oral informed consent was sought from all participants. Each participant was assured of utmost confidentiality and privacy. Cross-tabulations were performed in STATA 18 to determine the distribution of the prevalence of violence. Also, bivariable and multivariable logistic regression models were fitted to establish association between the participants’ characteristics and odds of experiencing violence. Results Overall, 457 (35.32%) women living with disabilities had ever experienced violence at a point in their lifetime. Psychological/emotional violence was the most prevalent violence (74.40%) followed by physical violence (31.07%) and denial of services (28.67%). Age was positively associated with the likelihood of experiencing violence. Women belonging to the Brahman/Chhetri ethnic group had reduced odds of violence [AOR = 0.56; 95%CI: 0.37–0.85] compared to Hill Dalits. Divorced or separated women showed a markedly higher likelihood of experiencing violence [AOR = 6.69; 95%CI: 2.31–19.40] compared to currently married women. Participants who had not witnessed violence against other women exhibited significantly higher odds of experiencing violence [AOR = 1.86; 95%CI: 1.20–2.89]. Women living in the Koshi province [AOR = 4.04; 95%CI: 2.54–6.42], Madhesh province [AOR = 2.16; 95%CI: 1.15–4.08] and Bagmati province [AOR = 2.21; 95%CI: 1.41–3.46] reported significantly higher odds of experiencing violence compared to those in Karnali. Conclusion The study concludes that age, ethnicity, marital status, and provincial residence are significant predictors of violence among women living with disability in Nepal. Interventions aimed at addressing violence against women living with disability in Nepal must prioritize older women and those who were previously married. Also, priority must be given to Koshi, Madhesh and Bagmati provinces where the prevalence and risk of experiencing violence is highest.